Orientalist Encounters at School: Security and Inclusion in the Education of Syrian Refugee Children in Istanbul - Şule Can Sayar; Taha Baran (Journal of Economy Culture and Society)
After the Syrian crisis, the number of Syrian refugees in Turkey is estimated to be approximately four million. Currently, one of the most significant aspects of the integration process of refugees in Turkey is the education of refugee students. Investigating the process of the co-education of refugee and Turkish citizen students in public schools provides some insight into what the future might hold for these refugees and sheds light on the dynamics of living together with locals. The first aim of this research is to explore the reception of the refugee students by the teachers in order to understand inclusion and/or exclusion mechanisms in education. Second, this study examines the roles that ethno-religious and political identities play in relations between teachers and refugee students by focusing on ethno-religious identity and discrimination. Drawing on the debates on orientalism and securitization in migration, it explicates the ways in which teachers justify their judgments and impressions of the refugee students through orientalist codes. To achieve this, public school teachers from two districts of Istanbul were invited to take part in this ethnographic research which was conducted in 2018.